The Role of Risk Management in Achieving Branch Office KPIs in Bank X - Nabil, Gymnastiar El; Diyanty, Vera (E-Jurnal Akuntansi, 2025)
This study aims to analyze the role of risk management in achieving Key Performance Indicators (KPI) at Bank X branches. A qualitative approach with a case study method was used, with data collection through questionnaires, in-depth interviews, and document analysis. The results of the study indicate that although risk policies have been designed in an integrated manner at the head office level, their implementation at the branch level faces challenges in the form of inequality in understanding risk, limited human resources and technology that is not yet optimal. Meanwhile, budget and communication have been running well. The risk management paradigm is often seen as a compliance tool rather than a proactive strategy to support the achievement of organizational targets. This study recommends the development of risk-based KPI indicators to create a more holistic and fair performance evaluation, strengthen the relationship between risk strategy and organizational performance, and build a more risk-aware organizational culture. Keywords: Risk Management; Key Performance Indicators (KPI); Banking; Performance Evaluation